THE ROAD TO PROJECT SUCCESS: EXPLORING PROJECT PLANNING IN THE SDF PROJECT PHASE I, KIGALI CITY, RWANDA - Alphonse, Tuyizere de Dieu; Valens, Jean (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
The main purpose of this study is to investigate the effect of project planning practices on the success of Skills Development Fund (SDF) project, Phase I in Kigali City. The target population comprises of SDF Staff, SDF funded project and SDF funded project beneficiaries and make a total number of 670 participants. The sample size was selected using Slovin’s formula and this makes a total number of 251 respondents. Descriptive and correlational research designs were used. Both open and ended questionnaire were used to collect data along with interview and observation. The collected data were entered and analysed using descriptive and inferential statistics. Pearson Correlation and Multiple Regression analysis were applied to analysed the effect of project planning on project success. Qualitative data made use of narrative analysis. The data were presented, analysed and interpreted in line with research objectives and hypotheses. On the effect of project scope planning on the success of SDF funded project Phase I in Kigali City, the results reveals a strong relationship between the project scope planning and project success as shown by R-Square (0.72) and further shows that the project success is at 72 % caused by the clear scope planning. Regarding the effect of schedule planning on the success of SDF funded project Phase I in Kigali City, it was realized that there is a strong relationship between the schedule planning and project success and that the project success is 66.4% due to schedule planning practices. For the effect of resource planning on the success of SDF funded project Phase I in Kigali City, the test shows a strong relationship between the resource planning practice and project success and that 84.2% of project success is due to resource planning practice. It was concluded that project scope planning, schedule planning and resource planning have a strong relationship with project success and have influenced the project success at the level of beyond 70%. It was suggested to SDF Fund to timely plan and deliver the package to the beneficiaries for the efficiency and effectiveness and to consider the different sections of the population for inclusive social and economic change